The Role of Speculation in the Determination of Energy Prices - Mustapha, Umar M. (International Journal of Energy Economics and Policy, 2012)
This paper seeks to evaluate the role of speculation in the determination of global energy prices. Designed as a case study, five major oil producing countries are the focus of this positivistic study: Nigeria, Mexico, Iran, Saudi Arabia and Russia. Data is collected through secondary sources. One-tailed and two-tailed tests carried out on the relationship between speculation and oil prices for each of the five countries yield critical values lower than the alpha. Thus, the null hypothesis is rejected in favor of the alternate hypothesis that ‘there is a significant and positive correlation between commodity derivatives (oil futures) and oil prices’. The study found that while there is a positive relationship between speculation in the commodity derivatives market and oil prices, such a relationship is at best weak and attributes the high prices to several factors, including political instability, high and rising demand from overheating economies such as China, and falling production levels, among others. The paper emphasized the need to enhance the physical and financial transparency of the energy market, as well as the operation of the supply and demand fundamentals, including regulating against insider trading and market manipulation practices, strengthening the reporting requirements of the dealers in the market, and strengthening capital adequacy and margin requirements. Keywords: Oil Futures; Derivatives; Markets Supply and Demand; Oil Producing Countries. JEL Classifications: Q31; Q02; Q41; Q47